Analysis of Factors Causing Students' Learning Difficulties in Indonesian Language Learning in Grade II of SD Negeri Kampung Lapai Padang - Silva, Mardatul; Efendi , Nofriza; Oktira, Yona Syaida; Azwar, Rica (The Future of Education Journal, 2025)
Learning difficulties are a problem that causes a student to not be able to follow the learning process well and not be able to achieve the expected learning objectives. This study aims to describe the factors causing learning difficulties experienced by second-grade students at Kampung Lapai Public Elementary School. This study uses a qualitative approach, a case study type. The research subjects are second-grade homeroom teachers and second-grade students. Data collection techniques through observation, interviews and documentation. Furthermore, data analysis through the stages of data reduction, data presentation, drawing conclusions. Based on the research results obtained, there are two factors causing student learning difficulties, namely (1) internal factors including intellectual abilities, lack of learning motivation, attitudes of not wanting to pay attention when studying. (2) external factors including: family factors, school factors, community factor.